Static absorber modelling - Đekić, Milica D. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: A static absorber is capable of neutralizing any signal either in the physical or virtual domain and its analysis will be presented in this paper.Methods: The approach used here includes purely scientific thoughts as well as a model with its explanations evaluated step by step applying highly sophisticated computer tools for design and simulation. No empirical results will be attached, only claims with their evidence.Results: The crucial outcome of this research is a completely new approach to binary systems that are now observed as a set of real numbers.Conclusion: The purpose of this research is to introduce something brand- new that can be used in cyber industry while a dynamic variation of the absorber is still under development.
Keywords: cyber defense; intelligence; static absorber; signal ban; hacking; singularity; mathematical modelling